1996
DOI: 10.1177/0734371x9601600202
|View full text |Cite
|
Sign up to set email alerts
|

Underground Merit Systems and the Balance Between Service and Compliance

Abstract: Current advocates of "reinvented" government call for more responsiveness to the needs of customers. This is true for internal as well as external customers, including government agencies seeking services from central personnel offices. Most states have adopted merit systems as a way to ensure open and competitive hiring for governmental service. The numerous rules and regulations that accompany these merit systems make the process of hiring qualified individuals slow and cumbersome and do not always ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Second, the effects of overregulation in personnel administration have been well-documented. Also, it has been shown that the frustration inherent to these conditions has led some public managers to undertake questionable administrative practices, including: hiring temporaries outside of normal civil service channels and converting them to permanent status, tailoring job de-scriptions so that a favored candidate is ensured of receiving a job, and &dquo;soliciting decli-nations&dquo; so that candidates that rank higher on certification lists will withdraw and other candidates (lower on the list) can be reached (see Ban, 1995;Ospina,1992;Ban & Riccucci, 1997;Jorgensen, Fairless, & Patton, 1996). For example, traditional personnel practices have been criticized for rewarding seniority rather than merit, giving employees too much job security, and preventing managers from rewarding good performance or correcting bad performance (see Cohen & Eimicke, 1994;Winter Commission, 1993; DiIulio, Garvey, & Kettl, 1993;Horner, 1988).…”
Section: Previous Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the effects of overregulation in personnel administration have been well-documented. Also, it has been shown that the frustration inherent to these conditions has led some public managers to undertake questionable administrative practices, including: hiring temporaries outside of normal civil service channels and converting them to permanent status, tailoring job de-scriptions so that a favored candidate is ensured of receiving a job, and &dquo;soliciting decli-nations&dquo; so that candidates that rank higher on certification lists will withdraw and other candidates (lower on the list) can be reached (see Ban, 1995;Ospina,1992;Ban & Riccucci, 1997;Jorgensen, Fairless, & Patton, 1996). For example, traditional personnel practices have been criticized for rewarding seniority rather than merit, giving employees too much job security, and preventing managers from rewarding good performance or correcting bad performance (see Cohen & Eimicke, 1994;Winter Commission, 1993; DiIulio, Garvey, & Kettl, 1993;Horner, 1988).…”
Section: Previous Inquirymentioning
confidence: 99%
“…Given this, it is little wonder that government's hiring processes have been said to send a &dquo;welcome to the funhouse&dquo; message to would-be public servants (Gore, 1996); such a message makes careers in public service unattractive to qualified individuals (Ink, 1983;DiIulio, 1994). Also, it has been shown that the frustration inherent to these conditions has led some public managers to undertake questionable administrative practices, including: hiring temporaries outside of normal civil service channels and converting them to permanent status, tailoring job de-scriptions so that a favored candidate is ensured of receiving a job, and &dquo;soliciting decli-nations&dquo; so that candidates that rank higher on certification lists will withdraw and other candidates (lower on the list) can be reached (see Ban, 1995;Ospina,1992;Ban & Riccucci, 1997;Jorgensen, Fairless, & Patton, 1996). Clearly, this literature paints a compelling case for change.…”
Section: Previous Inquirymentioning
confidence: 99%